Also No Support for the Youth Bias: Reply to Koppel and Berntsen. Issue 1 (10th October 2014) - Janssen, Steve M. J.
Summary In this reply, I discuss three reasons why the results of Koppel and Berntsen's original study and my study do not offer support for the youth bias. First, participants in Koppel and Berntsen's original study could have used their own memories of public events to indicate how old a typical person would most likely be when the most important public event during that person's life would occur. Second, the absence of the age effect in the second experiment seemed to be caused by the lack of power, making it unlikely that the expectations about the timing of important public events are shared by younger and older participants. Third, participants in my study expected that more events would occur in the period in which a prototypical person would be between 0 and 10 years old than in the period in which the person would be between 11 and 30 years old. Copyright © 2014 John Wiley & Sons, Ltd.